Cinematheraphy dalam Islam - Muh Azharmubarak (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
Cinematherapy is one of various techniques in therapy, but in this paper the researcher tries to combine cinematherapy techniques and the use of Islamic films in cinematherapy techniques. This study has a purpose, namely, to analyze the development of cinematherapy to help clients, and the lack of specific references that discuss cinematherapy in a religious context. Therefore, this research is here to try to contribute in the academic and social sciences in terms of counseling guidance so that it can contribute to the development of cinematherapy in Islam. The method used in this research is library research from the findings of journals that specifically discuss cinematherapy problems, namely 16 journals obtained through geoogle schoolar, garuda journals, sinta journals, and various searches found. The results of the study found that the cinematherapy technique has a high success rate in terms of general scientific fields but specifically the use of cinematherapy in Islam to overcome client problems has not been found. Therefore, researchers are trying to present Islamic values ​​in cinematherapy techniques as a form of scientific development in the form of cinematherapy as techniques and methods in overcoming client problems Keywords: therapy, film, cinematherapy, islam